1976
DOI: 10.1007/bf00570270
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorvos ? a 2-year inhalation carcinogenesis study in rats

Abstract: To determine the effects of dichlorvos vapour on the tumour incidence in rats, 5 week old Carworth Farm E strain rats weighing between 94 and 150 g were exposed to 0, 0.05, 0.5 and 5.0 mg/m3 in a 2-year inhalation study. The growth rate of all treated rats was depressed, particularly in the males. There was increased survival of the rats exposed to 5 mg/m3. There were no consistent differences in food intakes, organ weights, haematological or blood chemistry estimations, except in cholinesterase activites, amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
2
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 14 publications
0
25
2
1
Order By: Relevance
“…The difference in the route and duration of administration of DDVP in their study might be responsible for the observed difference in our findings. Our findings, also did not agree with that of Blair et al (1976), who in a similar inhalational study, reported that microscopic examinations of the DDVP toxicity could not be correlated with exposure to DDVP. Our earlier experiment indicated that tissue to exposure increases in its intensity with the duration as demonstrated in the lungs and the liver of DDVP-exposed rats .…”
Section: Discussioncontrasting
confidence: 99%
“…The difference in the route and duration of administration of DDVP in their study might be responsible for the observed difference in our findings. Our findings, also did not agree with that of Blair et al (1976), who in a similar inhalational study, reported that microscopic examinations of the DDVP toxicity could not be correlated with exposure to DDVP. Our earlier experiment indicated that tissue to exposure increases in its intensity with the duration as demonstrated in the lungs and the liver of DDVP-exposed rats .…”
Section: Discussioncontrasting
confidence: 99%
“…2 and 3), certain tissue and tumor codes are given in capital letters; these denote particular mixes of sites or tumor types from the NCI/NTP bioassays; capital letters are not used for other sources of data. When these capitals appear, additional information about the specific pathology is presented on the right side of the plot, where the header line reads "Citation or Pathology" in field (27). These special capitalized codes are used in the plot when the calculation of TD50 is based on special mixes of tissue and tumor types from the NCI/NTP bioassays.…”
Section: Range Of Carcinogenic Potencymentioning
confidence: 99%
“…Thus in the example given here, lines ld, e, and f, report for mice the TBA MXB, liv MXB, and then lun MXB. The specific pathology is given for liv MXB and lun MXB under column (27).…”
Section: Range Of Carcinogenic Potencymentioning
confidence: 99%
See 2 more Smart Citations